Upaya Meningkatkan Hasil Belajar IPA Dengan Menggunakan Model Pembelajaran Inkuiri Terbimbing Berbantuan Media Audio Visual: Efforts To Improve Science Learning Outcomes Using A Guided Inquiry Learning Model Assisted By Audio Visual Media - Dian Riyan Mike Triana; Rita Rahmaniati; Nurul Hikmah Kartini (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2023)
This research aims to: (1) Describe students' learning activities using the guided inquiry learning model assisted by audio-visual media for VA class students at SDN 4 Menteng. (2) Describe the activities of educators using the guided inquiry learning model assisted by audio-visual media for VA class students at SDN 4 Menteng. (3) Improving science learning outcomes for VA class students at SDN 4 Menteng by using a guided inquiry learning model assisted by audio-visual media. The subjects of this research were VA class students at SDN 4 Menteng. This type of research is Classroom Action Research. The data collection techniques used are observation and tests. The data analysis used is qualitative and quantitative analysis. The results of this research show that: (1) Students' learning activities when learning science on human circulatory system material using a guided inquiry learning model assisted by audio-visual media in the VA class at SDN 4 Menteng with good criteria. This can be seen as the more active students are in participating in learning activities. In cycle I, student learning activities obtained an average score of 4.1 and in cycle II, student learning activities obtained an average score of 4.7. (2) Educator activities during science learning on human circulatory system material using a guided inquiry learning model assisted by audio-visual media in the VA class at SDN 4 Menteng with good criteria. This can be seen from the learning process becoming more active and focused.